Prefrontal cortex stimulation normalizes deficient adaptive learning from outcome contingencies in low mood - Verena Sarrazin; Margot Juliëtte Overman; Luca Mezossy-Dona; Michael Browning; Jacinta O’Shea (Translational Psychiatry)
Abstract Depression and anxiety are associated with deficits in adjusting learning behaviour to changing outcome contingencies. This is likely to drive and maintain symptoms, for instance, by perpetuating negative biases or a sense of uncontrollability. Normalising such deficits in adaptive learning might therefore be a novel treatment target for affective disorders. The aim of this experimental medicine study was to test whether prefrontal cortex transcranial direct current stimulation (tDCS) could normalise these aberrant learning processes in depressed mood. To test proof-of-concept, we combined tDCS with a decision-making paradigm that manipulates the volatility of reward and punishment associations. 85 participants with low mood received tDCS during (or before) the task. In two sessions participants received real or sham tDCS in counter-balanced order. Compared to healthy controls (n = 40), individuals with low mood showed significantly impaired adjustment of learning rates to the volatility of loss outcomes. Prefrontal tDCS applied during task performance normalised this deficit, by increasing the adjustment of loss learning rates. As predicted, prefrontal tDCS before task performance (control) had no effect. Thus, the effect was cognitive-state dependent. Our study shows, for the first time, that a candidate depression treatment, prefrontal tDCS, when paired with a task, can reverse deficits in adaptive learning from outcome contingencies in low mood. Thus, combining neurostimulation with a concurrent cognitive manipulation is a potential novel strategy to enhance the effect of tDCS in depression treatment.